Engagement and attrition in Internet smoking cessation interventions: Insights from a cross-sectional survey of “one-hit-wonders” - Jessie E. Saul; Michael S. Amato; Sarah Cha; Amanda L. Graham (Internet Interventions, 2016)
Introduction: Internet interventions can reach large numbers of individuals. However, low levels of engagement and high rates of follow-up attrition are common, presenting major challenges to evaluation. This study investigated why registrants of an Internet smoking cessation intervention did not return after joining (“one hit wonders”), and explored the impact of graduated incentives on survey response rates and responder characteristics. Methods: A sample of “one hit wonders” that registered on a free smoking cessation website between 2014 and 2015 were surveyed. The initial invitation contained no incentive. Subsequent invitations were sent to random subsamples of non-responders from each previous wave offering $25 and $50 respectively. Descriptive statistics characterized respondents on demographic characteristics, reasons for not returning, and length of time since last visit. Differences were investigated with Fisher's Exact tests, Kruskal-Wallis, and logistic regression. Results: Of 8779 users who received the initial invitation, 132 completed the survey (1.5%). Among those subsequently offered a $25 incentive, 127 (3.7%) responded. Among those offered a $50 incentive, 97 responded (5.7%). The most common reasons endorsed for not returning were being unable to quit (51%), not having enough time (33%), having forgotten about the website (28%), and not being ready to quit (21%). Notably, however, 23% reported not returning because they had successfully quit smoking. Paid incentives yielded a higher proportion of individuals who were still smoking than the $0 incentive (72% vs. 61%). Among $0 and $25 responders, likelihood of survey response decreased with time since registration; the $50 incentive removed the negative effect of time-since-registration on probability of response. Conclusions: One third of participants that had disengaged from an Internet intervention reported abstinence at follow-up, suggesting that low levels of engagement are not synonymous with treatment failure in all cases. Paid incentives above $25 may be needed to elicit survey responses, especially among those with longer intervals of disengagement from an intervention.